Tаlаbаlаrgа ta’lim bеrish kоmреtеnsiуаsini shаkllаntirishdа intеrаktiv mеtоdlаrdаn fоуdаlаnish tехnоlоgiуаlаrining bugungi аmаliу shаkllаri, usullаri vа vоsitаlаri (rus tilini o‘qitish misolida) - Nazirova Zilola Rasulovna, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
To achieve a high level of foreign language proficiency, it is essential to study it thoroughly, particularly in higher education institutions. The primary goal of a teacher is to teach Russian at a professional level, requiring the implementation of the best teaching methods and mastery of the latest foreign language teaching technologies, including specialized educational technologies and approaches. This article examines the ways to achieve intensive teaching of Russian as a foreign language using modern practical forms, methods, and tools, with a focus on the use of interactive methods in shaping the content of Russian language instruction.